Detoxifier - Liver Care with Homoeopathic Modality (Homoeopathy for All, 2022)
The liver is the largest gland in the body situated below the diaphragm, on the right side of the abdomen and has many vital functions to perform for the body. It filters the blood coming from the digestive tract before it passes to the body. Other important functions of the liver are metabolism of carbohydrates, proteins, lipids and amino acids in the body; production of bile that help in breaking down the fat and detoxification of chemicals and drugs. Its other functions include producing blood clotting factors, storage of glucose and clearance of bilirubin. In this article we discuss about the major factor that affect the normal functioning of liver - Alcoholic liver disease.
Keywords: disease; chemicals; largest